2023
DOI: 10.1186/s12879-023-08046-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of early platelet dynamics in Staphylococcus aureus bacteremia

Abstract: Background Platelets are recognized as key immune effectors, but they are targets of bacterial virulence factors. In the present study, we aimed to examine the relationship between early platelet dynamics and the outcome of Staphylococcus aureus bacteremia (SAB). Method Electronic medical records of adult patients hospitalized for SAB between July 2012 and November 2020 were retrospectively reviewed for relevant demographic, laboratory, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Consistent with the BLOOMY score [ 7 ], the clinical condition on day 0 and day 3 (as demonstrated in Model IV) had been evidenced as the crucial determinates of short-term fatality. Moreover, similar to updated reports that highlighted the importance of dynamic vital signs and laboratory data in predicting short-term mortality among septic or bacteraemic individuals [ 27 , 28 ], the changed variables form day 0 to day 3 (as the component in Model IV) were recognised as the powerful determinants of 30-day mortality, in terms of the changes in the conscious level, respiratory condition, and hemodynamic status, which can be recognised as the responses to prompt antimicrobial therapy and early resuscitation.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with the BLOOMY score [ 7 ], the clinical condition on day 0 and day 3 (as demonstrated in Model IV) had been evidenced as the crucial determinates of short-term fatality. Moreover, similar to updated reports that highlighted the importance of dynamic vital signs and laboratory data in predicting short-term mortality among septic or bacteraemic individuals [ 27 , 28 ], the changed variables form day 0 to day 3 (as the component in Model IV) were recognised as the powerful determinants of 30-day mortality, in terms of the changes in the conscious level, respiratory condition, and hemodynamic status, which can be recognised as the responses to prompt antimicrobial therapy and early resuscitation.…”
Section: Discussionsupporting
confidence: 69%
“…We have previously shown that patients who experienced TC on day 1 of bloodstream infection may recover by day 4 while others who had normal platelet counts on day 1 may develop TC on day 4 depending on the degree of Hla production of the infecting strain and that TC on day 4 was significantly associated with mortality [ 23 ]. A total of 539 images taken with a smartphone representing growth of 229 unique isolates on SBA were employed.…”
Section: Resultsmentioning
confidence: 99%
“…Septic patients often exhibit abnormal activation and over-consumption of platelets, which subsequently lead to thrombocytopenia, thereby increasing bleeding risk [ 12 ]. Results from multiple studies have described the prognostic value of early changes in platelet count in septic patients [ 11 , 13 ]. However, the relationship between trajectories of repeated measures of platelet count collected from daily clinical practice and the prognosis of septic patients is not yet clear.…”
Section: Introductionmentioning
confidence: 99%